Carbon-free synthesis and luminescence saturation in a thick YAG:Ce film for laser-driven white lighting. Issue 2 (February 2019) - Xu, Jian; Hu, Baofu; Xu, Chao; Wang, Jian; Liu, Bingguo; Li, Hui; Wang, Xinliang; Du, Baoli; Gong, Yuxuan
Abstract: Good thermal dispersion is essential for phosphors used in laser-lighting applications. Luminescent films naturally show better thermal dispersion than bulk phosphor because the distance to the supporting substrate is shorter, which facilitates heat dissipation. However, the underlying mechanism for luminescence saturation in films is still unclear. In addition, the synthesis of luminescent films always involves the use of carbon-rich organic materials, which can introduce both pores and carbon residues. Here, we present a facile sol–gel route to synthesize YAG:Ce thick films suitable for laser lighting applications. Inorganic aluminum hydroxides are used as gelling agent, which solves the carbon residue problem. A series of YAG:Ce films of different thicknesses was produced at relatively low temperature (975 °C). The YAG:Ce film shows no luminescence saturation under 4.1 W blue laser excitation. This means this approach represents a strong potential candidate for applications like automotive headlamps and many other devices.